Melon with a Twist: A Case of Nicotine Overdose After Ingestion and Aspiration of Vape Liquid. Issue 1 (30th January 2021) - Jude, Joseph; Hiller, Hugh; Miller, Joel
ABSTRACT: We present the case of an active duty 21-year-old male with severe hypoxic respiratory failure after accidentally ingesting, and subsequently aspirating, vaping liquid while intoxicated. Because of the increasing prevalence of vaping devices, this case highlights a unique risk of vape liquids with concentrated nicotine levels and appetizing labels and aromas. Vaping-associated pulmonary injury has been previously described in multiple publications, but unlike those patients with pathology after inhaling vaping products, our patient ingested and subsequently aspirated the highly nicotinic substance. Most vape liquid products have enough nicotine to result in significant toxicity, which most concerningly can lead to nicotine-induced respiratory failure. This patient's hypoxia appeared to be multifactorial as a result of both nicotine toxicity and aspiration, but ultimately treatment of both focused on supportive measures.In addition to understanding nicotine toxicity, this patient's hypoxia secondary to agitation and aspiration requiring emergent airway management illustrates the importance of understanding the technique of Delayed Sequence Intubation and its proper application in the critical airway algorithm. By treating preoxygenation as a procedure, the patient received adequate oxygenation resulting in successful intubation without harmful desaturation during the procedure.Given the prevalence of tobacco use in the military as well as the increasing popularity of vaping devices, future military providers have a responsibility to their patients to be prepared for similar case presentations. Fortunately, this case demonstrates that when managed properly, otherwise healthy patients without comorbidities often recover without significant long-term sequelae.